Treatments of Choice for Isolated, Full-Thickness Tears of the Posterior Cruciate Ligament: A Nationwide Survey of Orthopaedic Surgeons - Schumaier, Adam; Minoughan, Chelsea; Jimenez, Andrew; Grawe, Brian (The Journal of Knee Surgery, 2019)
The ideal treatment for isolated, full-thickness tears of the posterior cruciate ligament (PCL) is uncertain. The purpose of this study was to determine how the majority of orthopaedic surgeons treat isolated, full-thickness tears of the PCL. In July 2017, a 17-question multiple-choice survey regarding the treatment of isolated, full-thickness tears of the PCL was emailed to 3,500 orthopaedic sports medicine surgeons with membership in the American Orthopaedic Society for Sports Medicine. Responders answered multiple-choice questions related to indications, technique, graft choice, bracing, and weight-bearing status following reconstruction. Answer choices were then analyzed against surgeon-specific variables. The survey was completed by 663 orthopaedic surgeons. Of the responders, 93% were fellowship trained in sports medicine with an average practice duration of 13 years. The total number of PCLs reconstructed per surgeon was low, 11.6. On average, surgeons estimate they reconstruct the PCL in only 22% of patients with full-thickness tears. The two most common surgical indications were functional limitations and failure of physical therapy. The reconstruction of choice involves a transtibial approach (63%) with a single bundle (87%) allograft (83%) of the Achilles tendon (51%). The postoperative brace is typically locked in extension (66%), and weight-bearing is delayed for 3.8 weeks. Of the surgeons with the fewest years of experience, 39% use all-inside, 89% use allograft, and 24% use dynamic bracing. Compared with surgeons with the most years of experience, only 16% use all-inside (p < 0.01), 57% use allograft (p < 0.01), and 11% use dynamic bracing (p = 0.01). Isolated, full-thickness tears of the PCL are rare injuries that are infrequently reconstructed. The most common indications for reconstruction are functional limitations and failure of conservative management. Most surgeons' treatment of choice for reconstruction involves a transtibial approach with a single bundle Achilles allograft and a postoperative brace locked in extension. On average, weight-bearing is prolonged for 3.8 weeks. The all-inside technique, allograft, and dynamic bracing are becoming more popular.
Keywords: posterior cruciate ligament; multiligamentous injury; transtibial; all-inside; single bundle; double bundle